Ohmic treatment of fresh foods: effect on textural properties - Olivera, Daniela Flavia (2013)
The aim of this work was to verify the effects of ohmic heating (OH) treatment on texture of fresh solid food (without pre-treatment in brine solutions), subjected to constant electrical field gradient (1100 V/m; 2200 V/m; 3300 V/m). Samples of fresh potatoes, carrots and apples cut into cylinders (d = 30 mm, h = 9.0 mm) underwent OH for 60, 120, 180 and 240 seconds. Texture measurements were performed in a universal testing machine Instron 4301, with a 100 N load cell, using a single-cycle compression test. The raw untreated sample was used as control. Stress–deformation behavior of food samples processed by OH differs appreciably from raw untreated samples for all cooking times. Firmness of solid samples decreased with OH time. This study confirmed that OH significantly affects texture of solid foods, producing structural damage, even though food has a low electrical conductivity.